Proliferación y viabilidad celular de una membrana de policaprolactona (pcl) e hidroxiapatita (ha) sobre fibroblastos del ligamento periodontal: revisión de alcance (2021)
Periodontal ligament is a not mineralized connective tissue, it contains a stem cells population. Its regeneration can be achieved thanksto the cell proliferation and viability. Although there is evidence about the use of biomterials in periodontal regeneration they propose the PCL(polycaprolactone) and Hydroxyapatite (HA) as the aim of this review, in as much as they have proved having meaning advantages overall, becoming them into investigation target toward future biomaterials elaboration which only dont have mechanical and rheological properties according to oral environment but also regenerative and immunomodulatory properties. The aim of this review was summarizing the current knowledge found in the literature about the cytotoxic effects of polycaprolactone and hydroxyapatite on fibroblasts of the periodontal ligament.